Community deployment of metofluthrin emanators to control indoor Aedes aegypti: Efficacy results from a crossover trial in Yucatan, Mexico - Che-Mendoza, Azael; Guillermo-May, Guillermo; Kirstein, Oscar D.; Chi-Ku, Aylin; Pavía-Ruz, Norma; Medina-Barreiro, Anuar; González-Olvera, Gabriela; Devine, Gregor; Vazquez-Prokopec, Gonzalo; Manrique-Saide, Pablo (PLOS Neglected Tropical Diseases, 2025)
Background Spatial emanators (SE) are innovative tools for controlling indoor Aedes aegypti due to their relatively easy use and high efficacy. Large-scale implementation challenges include community adoption, particularly ensuring proper installation and timely replacement as SE efficacy wanes. Methodology and principal findings We conducted a three-arm, open-label entomological cluster randomized controlled trial with a crossover design, involving 588 households, to assess the entomological effect of the community use of metofluthrin emanators. Arms were: “no treatment”; “community-led deployment” (CD), where the households were responsible for installing and replacing SE with minimal guidance; and “managed deployment” (MD), where the research team handled SE installation and replacement. Emanators were replaced every 3 weeks across four deployment cycles, followed by a crossover between the CD and MD arms. Indoor resting mosquitoes were collected using Prokopack aspirators, and human landing counts (HLCs) were conducted in a subset of 12 houses (4 by arm) at the first, fourth, fifth, and eighth SE replacement rounds. Values of each endpoint during all sampling periods were compared using generalized linear mixed effects models (GLMM), the coefficients of the best-fitting model estimated that SE intervention reduced the number of Ae. aegypti per house by 32.7% (95%CI = 16.2-46.0%) in the CD arm and 36.8% (21.1-49.3%) in the MD arm. HLCs accounted 74–94% efficacy (MD) and 35–79% (CD). The crossover analysis found no significant difference between periods and arms, demonstrating the community’s ability to manage SE as effectively as research team, even without prior training. Conclusions/significance This trial suggests that safe, portable SE are suited to deployment by householders as a rapid response to local Aedes-borne disease outbreaks even in the presence of high pyrethroid resistance in the local Aedes population. In urban areas where effective coverage and resourcing is a challenge to control campaigns, community “ownership” of SE products may enhance the impact of insecticidal interventions.